ANALYSIS OF FLYPAPER EFFECT REVENUE SHARING FUND (DBH) AND REGIONALLY GENERATED REVENUE (PAD) TOWARD CAPITAL EXPENDITURE BY DISTRICT / TOWN IN SOUTH SUMATERA 2009-2011 - Marliana, Marliana; Mukhtaruddin, Mukhtaruddin; Ferina, Ika Sasti (Jurnal Akuntansi, Fakultas Ekonomi, Universitas Sriwijaya, 2012)
This research aims to identify the influence of Flypaper Effect Revenue Sharing Fund (DBH) and Regionally Generated Revenue (PAD) toward capital expenditure by District / Town in South Sumatra 2009-2011. The population in this research was all of District / Town in South Sumatera in 2009 until 2011 and can be accessed at www.djpk.depkeu.go.id Site. Total Sample in this research is 15 districts /towns which consist of 11 districts and 4 towns in South Sumatera. Data were analyzed with tests of classic assumption and examination of hypothesis with multiple linear regression method. Based on the F test results indicate that the DBH and the PAD have influence on capital expenditure. Then through t test shows that DBH showed an influence on the probability of capital expenditure under the = 5% (0.000). While the PAD has no effect on the profitability of capital expenditure above = 5% (0.60). From the results of this study also demonstrated the occurrence of flypaper in districts / towns in South Sumatera, but had no flypaper effect against capital expenditure forecast. Â Keywords: Capital Expenditure, Revenue Sharing Fund, Flypaper Effect, Regionally Generated Revenue